(untitled) - Meyerhoff, Marianne (Hoboken, N.J., 2007)
Lotte Meyerhoff's best friends risked their lives in Nazi Germany to safeguard these and other treasured heirlooms and mementos from her family and return them to her after the war. The Holocaust had left Lotte the lone survivor of her family, and these precious objects gave her back a crucial piece of her past. Four Girls from Berlin vividly recreates that past and tells the story of Lotte and her courageous non-Jewish friends Ilonka, Erica, and Ursula as they lived under the shadow of Hitler in Berlin.
Keywords: Jews, German,Người Do Thái, người Đức,Jewish refugees,Mothers and daughters; Người tị nạn Do Thái,Mẹ và con gái; California,Los Angeles,Los Angeles,California,California,Los Angeles,California,Los Angeles,California,Los Angeles,California,Los Angeles